New avenues for regional cooperation : tackling human trafficking in Asia - Cook, Alistair David Blair (2014)
In Southeast Asia, rising population and technological advances mean that unfortunately human traffickers have a growing target base online and are making greater use of technology. Nevertheless, creatively employing online tools provides an opportunity to counter cross-border trafficking.